Exciton effects in band-edge electroluminescence of silicon barrier structures - Sachenko, A.V.; Gorban, A.P.; Korbutyak, D.V.; Kostylyov, V.P.; Kryuchenko, Yu.V.; Chernenko, V.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2004)
A theoretical analysis of the band-edge electroluminescence efficiency in silicon diodes and p-i-n-structures has been made. We have shown that maximal possible efficiency can achieve 10 % both at room and liquid nitrogen temperatures. Maximal values of the efficiency are restricted by the interband Auger recombination process. It is found that electroluminescence efficiency decreases rapidly with the decrease of characteristic Shockley- Reed-Hall nonradiative lifetime for minority carriers. It is shown that even at room temperatures the main contribution into the edge electroluminescence in silicon barrier structures is given by excitonic effects. Dark I-V characteristics of directly biased silicon diodes measured both at room and nitrogen temperatures are used to explain anomalous temperature dependencies of silicon diode electroluminescence.